2016
DOI: 10.1186/s40900-016-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising target behaviours for research in diabetes: Using the nominal group technique to achieve consensus from key stakeholders

Abstract: Plain english summaryThe behaviour of people with diabetes (e.g. taking medication) and the behaviour of doctors and other healthcare professionals (e.g. checking patients’ blood sugar) are important. Our research group wanted to select one patient behaviour and one healthcare professional behaviour as topics to research in Ireland. Patients and healthcare professionals are not usually asked to help decide on research topics. In this study, we wanted to bring together patients, healthcare professionals and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
(42 reference statements)
0
25
0
Order By: Relevance
“…In line with international evidence, Irish audit data indicate that the number of people attending is far lower than the number of people newly diagnosed each year [12]. Consequently, a research prioritization exercise with people with diabetes, healthcare professionals and policy-makers identified improving attendance at structured Type 2 diabetes education programmes as a top priority for research in Ireland [13].…”
Section: Introductionmentioning
confidence: 93%
“…In line with international evidence, Irish audit data indicate that the number of people attending is far lower than the number of people newly diagnosed each year [12]. Consequently, a research prioritization exercise with people with diabetes, healthcare professionals and policy-makers identified improving attendance at structured Type 2 diabetes education programmes as a top priority for research in Ireland [13].…”
Section: Introductionmentioning
confidence: 93%
“…These strategies need to be carefully selected for the target audience and crucially, need to be implemented correctly [13]. In support of HCPs' role in goal-setting, a recent research prioritization involving key diabetes stakeholders identified 'goal-setting with patients' as a focus area for research in diabetes [14]. DSME providers are typically healthcare professionals (HCPs), responsible for translating the behaviour change content of programme manuals into practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, limited research has explored educators' perspectives on putting behaviour change elements such as goal-setting into practice. In support of HCPs' role in goal-setting, a recent research prioritization involving key diabetes stakeholders identified 'goal-setting with patients' as a focus area for research in diabetes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Research prioritization provides such a process, whereby key stakeholders generate ideas and move towards consensus on important research topics [43]. The prioritization process has been used to identify priorities across conditions and populations [26]. In the area of trials' research prioritization has been conducted with Directors of UK Clinical Research Collaboration Clinical Trials Units to inform the broader trials' methodological research agenda [49] and, more recently, a priority setting exercise has been reported to inform the global health trials' methodology research agenda [46].…”
Section: Introductionmentioning
confidence: 99%